Evaluation of an underfloor heating system installed in an educational-experimental module built with non-conventional materials on a small scale for higher education - Alpaca Rendón, Orlando Jesús (2022)
In  this case study, an experimental module of a water-based underfloor heating system, was developed for the thermo-fluids laboratory located in the Universidad Católica de Santa María, with the aim of confirming the possibility of correct emulation of the thermal principles of these type of heating systems within a short time of two hours maximum (due to the high thermal inertia of these systems and the limited time to carry out experimental procedures in laboratories of universities), all this using alternative materials that make easier the process of building and maintenance on a limited budget, while keeping the capability to carry through other experimental procedures related to underfloor heating systems. So that, a proper evaluation of the proposal to use a module to perform experimental procedures related to underfloor heating, can be made. To answer the question posed in this article, the experimental procedure on the module focuses primely on monitoring temperatures of the floor, water and test chamber as well as the time. Results show that using a water temperature of 60°C for 60 minutes, a temperature increase of 6.5°C is recorded in the test chamber, whereupon the heating system is shut down, and the chamber air is replaced, exists a temperature drop in the test chamber at a lower rate, with 1.1°C during 30 minutes. The module was developed in such a way that it can be manipulated via both, a user interface on a computer or without it.